Predicting toxicity in advanced lung cancer patients treated with platinum-based chemotherapy. (August 2013) - Ioannidis, Georgios; Souglakos, John; Georgoulias, Vassilis
SUMMARY Platinum-based chemotherapy is currently the state-of-the-art first-line cytotoxic treatment of advanced-stage small-cell lung cancers and non-small-cell lung cancers, but at the cost of potentially severe toxicity. As platinum-related adverse events may impede the success of palliative chemotherapy, while negatively affecting the patients' quality of life, treatment strategies should aim at optimizing the toxicity:benefit ratio. The identification and application of clinical and laboratory biomarkers, including pharamacogenetic tools, for reliably predicting toxicity in this setting would significantly contribute to such a customized approach. This is a comprehensive overview of the toxicity-prediction factors with the most potential, including ethnicity, age, gender, performance status, comorbidity and nutrition, as well as molecular biomarkers, such as germline genetic polymorphisms.